A novel kurtosis driven variable step-size adaptive algorithm - Pazaitis, D.I.; Constantinides, A.G. (IEEE transactions on signal processing, 1999)
A new variable step-size LMS filter is introduced. The time-varying step-size sequence is adjusted, utilizing the kurtosis of the estimation error, therefore reducing performance degradation due to the existence of strong noise. The convergence properties of the algorithm are analyzed, and an adaptive kurtosis estimator that takes into account noise statistics and optimally adapts itself is also presented. Simulation results confirm the algorithm's improved performance and flexibility.